EXAMINING THE RELATIONSHIP BETWEEN CONTINUING EDUCATION AND JOB PERFORMANCE AMONG NURSING TECHNICIANS IN KSA - Abdullah Ghanem Abdullah Alanazi, Maani Saud Hajad Aldhafeeri, Abdulhadi Abdulaziz Ali Almasara, Muhammad Lafi Mazloh Al-Ruwaili, Khalid Salem Sehlan Alrowaili, Bader Awad Zaidan Alrwily, (Chelonian Research Foundation, 2022)
Continuing education plays a crucial role in maintaining and enhancing the knowledge, skills, and competencies of healthcare professionals, including nursing technicians. This study aims to examine the relationship between continuing education and job performance among nursing technicians in Saudi Arabia. A cross-sectional survey was conducted among 500 nursing technicians working in various healthcare facilities across the country. The survey assessed participants' involvement in continuing education activities, their perceived impact on job performance, and their actual job performance ratings. Descriptive statistics, correlation analysis, and multiple regression were used to analyze the data. The findings revealed a significant positive relationship between continuing education and job performance, with those engaging in more continuing education activities displaying higher job performance ratings. The study highlights the importance of promoting and supporting continuing education for nursing technicians in KSA to improve the quality of patient care and overall healthcare outcomes.